Pandemi Covid-19 Sebagai Sumber Tema Dalam Pembelajaran Mata Kuliah Komposisi Tari di Program Studi Seni Pertunjukan Universitas PGRI Palembang - Rully Rochayati; Rio Eka Putra (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
The purpose of this research is to find out how the Covid-19 pandemic can be used as a source of themes in the learning process in the Dance Composition course. The source of the theme is a part that must be known for students so that in the process of creating dance they can produce good and quality work, considering that the source of the theme is the basic foundation that leads to the formation of basic concepts in dance work. The method used is descriptive qualitative data collection techniques, namely observation, interviews, literature study and recording. The result of the research that has been done is that the source of the theme cannot be formed if the source of the work and the source of ideas is not determined in advance. After both are found, students can determine the source of the story theme, and the source of the motion theme. Determining the source of the work, the source of ideas, the source of the theme of the story and the source of the theme of motion are parts that must be surpassed by students who take the dance composition course in the Performing Arts Education Study Program. The findings that have been made by students turned out to present interesting new ideas and creativity, even though the findings of the motion were simple ones.